QUALITY OF IRRIGATION WATER , FOLIAR APPLIED SELENIUM AND SOIL POLYMER IN IMPROVING VEGETATIVE AND FLOWERING CHARACTERISTICS OF IRIS PLANTS. - Istabraq. A. Aziz; Jawad, S. A. Abd Al-Latif (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The experiment was conducted in a green house at the Department of Horticulture and Landscaping design College of Agriculture engineering Sciences for the fall season 2020-2021 to determine the response of the Iris plant to bear the conditions of abiotic stresses by studying the effect of irrigation with saline water on the vegetative and flowering characteristics of the plant.The study included three factor, the first factor, the quality of irrigation water (main plots) and at three levels: (irrigation with water from the Tigris River 0.92 dm s-1(I0), alternating irrigation (one irrigation with saline water followed by irrigation with the water of the Tigris River(I1), Alternating irrigation (two irrigations with saline water, followed by irrigation with the water of the Tigris River(I2), The second factor is the addition of Polyacrylamide (0, 1.5,2.5) g of soil-1 his symbol(P0,P1.P2). The third factor is foliar applied selenium using three concentrations (0, 10,20) mg L-1 his symbol(S0,S1,S2) Results showed that that increasing salinity of irrigation water led to a decrease in all vegetative characteristics and flowering, increasing the efficacy of the enzyme Peroxidase and Proline, increasing both chlorine and sodium in the leaves. Spraying with selenium at a concentration of 20 mg L-1 as well as adding polymers at a concentration of 2.5 g led to an increase in the vegetative and flowering characteristics of the plant, reducing the elements chlorine and sodium in the leaves, and decreasing the effectiveness of the enzyme Peroxidase and Proline.